Reduction of basal plane defects in (11–22) semipolar InGaN/GaN MQWs fabricated on patterned (113) Si substrates by introducing AlGaN barrier layers. Issue 8 (22nd March 2017) - Uesugi, Kenjiro; Hikosaka, Toshiki; Ono, Hiroshi; Sakano, Tatsunori; Nunoue, Shinya
Abstract : GaN grown on nonpolar or semipolar faces have been widely developed as a promising material for the next generation optical and electronic devices. In this work, (11–22) semipolar InGaN/GaN MQWs were grown on patterned (113) Si substrates and fabricated into thin‐film‐type flip‐chip LEDs. From CL and TEM measurement, generation of basal plane defects (BPDs) around MQWs and Strain‐relaxation layers (SRLs) has been observed. The relationship between MQW structures and formation of BPDs has been investigated. By optimizing MQW structures, light output power and external quantum efficiency have been improved with thick InGaN well layers and GaN barrier layers. Introducing AlGaN barrier layers has enabled further reduction of BPDs in MQWs and, as a result, an enhancement of EQE has been achieved. The maximum EQE value of the sample with AlGaN barrier layers was 12.9%.This result indicates that the reduction of BPDs is an effective approach for obtaining the high‐efficiency semipolar LEDs on Si substrates.